Digital Platform Mapping: Moslem Family Education Content on Social Media - Sutrisno, Zulfa Zakhrofa; Azani, Mohammad Zakki; Dahlan, Budi Satriadi Samsul (Universitas Muhammadiyah Surakarta, 2024)
This study examines the basic theory of Islamic family education by adjusting technological developments through content mapping on social media platforms that focus on YouTube and TikTok with the aim of making it easier for Muslims to understand education in the family and select and sort content for their children and maximize the use of digital media as a means of implementing Islamic values in the family. The method used is qualitative with literature studies sourced from books as the main reference and supporting sources in the form of journals, scientific articles, survey data, and other relevant sources. Content analysis was conducted to identify the types of content available, including religious education materials in families, effective communication, and educational content for early childhood. The result of this study is the mapping of social media content as a sorting of educational social media content for Muslims, expected to provide a better understanding to the wider community about the types of Muslim family educational content available on digital platforms. The conclusion of this study is that education in the family plays an important role for a person's growth, therefore education is needed in accordance with the era of technological development that occurs today. The amount of non-educational content on social media often makes parents worry about their children accessing digital devices. Therefore, the author maps educational content that can be used as a learning resource for family education.